Disease Control Priorities, Third Edition (Volume 1): Essential Surgery 2015
DOI: 10.1596/978-1-4648-0346-8_ch4
|View full text |Cite
|
Sign up to set email alerts
|

General Surgical Emergencies

Abstract: Acute abdominal conditions Incarcerated and Strangulated Inguinal Hernias Appendicitis Intestinal obstruction Complications of peptic ulcer, including perforated ulcer and bleeding ulcer Bleeding from esophageal varices Pelvic infections with abscesses Perforated typhoid ulcers Amebic liver abscess Gall bladder and bile duct disease Respiratory obstruction, foreign bodies, and pleural disease Urinary obstruction caused by stricture, stone, or prostatic enlargement Surgical infections of the skin, muscles, bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In low and middle income countries (LMICs), studies has showed that at least 60 percent of the surgical operations are performed for emergency patients [9]. Our study also showed 61% of all major operations performed were for emergency conditions.…”
Section: Discussionsupporting
confidence: 68%
“…In low and middle income countries (LMICs), studies has showed that at least 60 percent of the surgical operations are performed for emergency patients [9]. Our study also showed 61% of all major operations performed were for emergency conditions.…”
Section: Discussionsupporting
confidence: 68%
“… 1 2 In low-income and middle-income countries, this figure rises to 60%. 3 Current evidence shows patients undergoing emergency surgery are three times more likely to die than those undergoing elective surgery. For those who survive, they are twice as likely to suffer a complication.…”
Section: Introductionmentioning
confidence: 99%
“…These addresses were added to lists and differentiated per federal state. From each list, 80 surgeons from first- and second-level hospitals (level I and II [community/general/regional hospitals]) and 20 surgeons from third-level hospitals (level III [central/University hospitals]) were randomly selected using the Microsoft Excel® function RANDBETWEEN(X;Y) [15]. The list of surgeons from “Bremen” was incorporated into “Lower Saxonia.” Another 80 + 20 surgeons were accordingly selected from hospitals in Germany’s 5 largest metropolitan areas (MET): Berlin, Munich, Hamburg, Cologne, and Frankfurt.…”
Section: Methodsmentioning
confidence: 99%